Poly(thioctic acid): From Bottom‐Up Self‐Assembly to 3D‐Fused Deposition Modeling Printing. Issue 33 (11th October 2022) - Cai, Changyong; Wu, Shuanggen; Zhang, Yunfei; Li, Fenfang; Tan, Zhijian; Dong, Shengyi
Abstract: Inspired by the bottom‐up assembly in nature, an artificial self‐assembly pattern is introduced into 3D‐fused deposition modeling (FDM) printing to achieve additive manufacturing on the macroscopic scale. Thermally activated polymerization of thioctic acid (TA ) enabled the bulk construction of poly(TA ), and yielded unique time‐dependent self‐assembly. Freshly prepared poly(TA ) can spontaneously and continuously transfer into higher‐molecular‐weight species and low‐molecular‐weight TA monomers. Poly(TA ) and the newly formed TA further assembled into self‐reinforcing materials via microscopic‐phase separation. Bottom‐up self‐assembly patterns on different scales are fully realized by 3D FDM printing of poly(TA ): thermally induced polymerization of TA (microscopic‐scale assembly) to poly(TA ) and 3D printing (macroscopic‐scale assembly) of poly(TA ) are simultaneously achieved in the 3D‐printing process; after 3D printing, the poly(TA ) modes show mechanically enhanced features over time, arising from the microscopic self‐assembly of poly(TA ) and TA . This study clearly demonstrates that micro‐ and macroscopic bottom‐up self‐assembly can be applied in 3D additive manufacturing. Abstract : Naturally inspired bottom‐up self‐assembly patterns on different scales are fully realized by 3D‐fused deposition modeling printing of poly(thioctic acid): thermally induced polymerization of thioctic acid to poly(thioctic acid) and 3D printing of poly(thioctic acid) are simultaneously achieved in the 3D‐printing process. After 3D printing, the poly(thioctic acid) modes show mechanically enhanced features over time, arising from the microscopic self‐assembly of poly(thioctic acid) and thioctic acid.